2013
DOI: 10.1038/onc.2013.184
|View full text |Cite|
|
Sign up to set email alerts
|

Osteopontin signaling upregulates cyclooxygenase-2 expression in tumor-associated macrophages leading to enhanced angiogenesis and melanoma growth via α9β1 integrin

Abstract: Tumor-associated macrophages (TAMs) have multifaceted roles in tumor development, particularly linked with tumor angiogenesis and invasion, but the molecular mechanism underlying this association remains unclear. In this study, we report that lack of osteopontin (OPN) suppresses melanoma growth in opn(-/-) mice and macrophages are the crucial component responsible for OPN-regulated melanoma growth. In tumor microenvironment, OPN activates macrophages and influences angiogenesis by enhancing cyclooxygenase-2 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 49 publications
2
128
0
2
Order By: Relevance
“…These results suggested that macrophage-like THP-1 cells facilitate angiogenesis in tumors to provide rapidly proliferating transformed-cells much more oxygen and nutrients. The proangiogenic role of TAMs has been characterized by previous studies that showed the correlation between TAMs infiltration and high number of vascular in many tumors, such as squamous cell carcinoma of the esophagus, prostate cancer and ameloblastoma (Koide et al, 2004;Halin et al, 2009;Guzman-Medrano et al, 2012), the main reason for this may be that TAMs produce many cytokines for angiogenesis: vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), TNF-α, transforming growth factor-β (TGF-β) (Bingle et al, 2006;Araujo et al, 2010;Shu et al, 2012), and several angiogenesis-modulating enzymes, such as matrix metalloproteinases (MMP) (Pollard, 2004;Kale et al, 2014). The fact that the specific proangiogenic program in tumor turns on indicated that tumor is in a condition of hypoxic, rendering tumor cells to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that macrophage-like THP-1 cells facilitate angiogenesis in tumors to provide rapidly proliferating transformed-cells much more oxygen and nutrients. The proangiogenic role of TAMs has been characterized by previous studies that showed the correlation between TAMs infiltration and high number of vascular in many tumors, such as squamous cell carcinoma of the esophagus, prostate cancer and ameloblastoma (Koide et al, 2004;Halin et al, 2009;Guzman-Medrano et al, 2012), the main reason for this may be that TAMs produce many cytokines for angiogenesis: vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), TNF-α, transforming growth factor-β (TGF-β) (Bingle et al, 2006;Araujo et al, 2010;Shu et al, 2012), and several angiogenesis-modulating enzymes, such as matrix metalloproteinases (MMP) (Pollard, 2004;Kale et al, 2014). The fact that the specific proangiogenic program in tumor turns on indicated that tumor is in a condition of hypoxic, rendering tumor cells to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin combined with PGE2 substantially increases the influence on angiogenesis by enhancing the expression of MMP-9 (36). Another study revealed that the increased expression of COX-2 in melanoma tumor types is associated with increased VEGF expression, density of micro vessels and inflammatory infiltration formed of macrophages (37,38).…”
Section: Macrophages In Skin Melanomasmentioning
confidence: 99%
“…Macrophages stimulated by osteopontin from the melanoma microenvironment start to synthesize the COX-2 protein (37). α9β1 integrin on macrophages is the receptor for osteopontin, which stimulates COX-2 expression in macrophages through the ERK and p38 pathways (37). In addition to maintaining inflammation, COX-2 additionally promotes melanoma cell migration and angiogenesis through the COX-2 dependent production of PGE2 (37).…”
Section: Macrophages In Skin Melanomasmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that melanoma cells can recruit macrophages and induce cyclooxygenase-2 expression, which leads to increased angiogenesis and tumour growth. 64 While they are probably not essential for tumour angiogenesis, TAMs certainly contribute to the speed of this process. 65 Several of those secreted factors, growth factors such EGF, VEGF and cytokines such as interleukin (IL)-10 and IL-23, also contribute to tumour growth and metastasis.…”
Section: Focus On Tumour-associated Macrophagesmentioning
confidence: 99%